Integrasi Ilmu dalam Islam Perspektif Quraish Shihab dan Relevansinya dengan Pengembangan Kurikulum Pendidikan Islam - Aulia, Rifka; Rossidy, Imron (Tarbiyatuna Kajian Pendidikan Islam, 2026)
The persistent separation between religious and secular sciences in contemporary Islamic education calls for an integrative framework grounded in authoritative Islamic scholarship. This study aims to analyze: (1) Quraish Shihab’s view on the integration of knowledge in Islam, (2) the relevance of this integration to Islamic education, and (3) its implications for Islamic education curriculum development. Using a qualitative approach through library research, it examines Shihab’s works and related literature. The findings show that, for Quraish Shihab, integration of knowledge is rooted in taw??d, which rejects an essential divide between religious and worldly sciences and demands synergy between revelation and reason. This integration is highly relevant for constructing a holistic, contextual, and future-oriented curriculum capable of forming ins?n k?mil who are knowledgeable, ethical, and moderate.